IMMIGRATION PERSPECTIVE ON FOREIGN EXPERT IN INDONESIAN LAW OF CRIMINAL PROCEDURE - Prima Setiawan (Polteknik Imigrasi, 2019)
The implementation of criminal law enforcement in Indonesia is based on criminal procedural law. Criminal Procedure Law is a formal law that is in the regulations regarding the provisions of the legal process. Proof processes as the legal means of proof based on Law Number 8 of 1981 shall be Witnesses Testimony, Expert Testimony, a Document, an Indication and Accused Testimony. Expert testimony has an important role in the Proof processes both from the level of investigation to the trial by the judge. In doing so, an expert can be a foreign national. Normative-empirical research by the method of legal research on legal instruments conducted to explain how the immigration perspective of experts who are foreign citizens. Experts who are citizens of foreign countries must have a residence permit stipulated in the Immigration Act, even though, it is a state order for someone who gives testimony as an expert in order to uphold the law as fairly as possible. To achieve this, as well as by not violating the immigration provisions for experts who are foreigner, the authors provide advice for law enforcers, both investigators, public prosecutors, judges and legal counsel to know and understand the immigration provisions that applied to foreigners as the experts in law enforcement process.